PENINGKATAN KETERAMPILAN SOSIAL DAN HASIL BELAJAR PADA MATERI MEMBANGUN MASYARAKAT YANG BERADAB MELALUI PENDEKATAN PROJECT BASED LEARNING PADA SISWA KELAS IV SDN BESAH II - Ariyanto, Riko; Wicaksono, Vicky Dwi; Handayani, Suci (MIDA : Jurnal Pendidikan Dasar Islam, 2024)
Implementation is carried out on the basis of the phenomenon that arises in Class IV SDN Besah II, where students lack good social skills. The research was conducted to find out whether the use of project-based learning models is effective in improving social skills and learning outcomes for students. With the presence of innovation using project-based learning to improve social skills and learning outcomes, students are expected to engage in a learning process that helps them improve their abilities. Research is carried out using class action research, or PTK, with class IV SDN Besah II research subjects. According to the results of the research that has been carried out, there was an improvement in the social skills and learning outcomes of the students in cycles I and II. In the aspect of social skills, there was an increase in success of 13,5% and 12%, while the learning outcome experienced an average increase of 78 to 88, where each cycle has already been above the KKM. Based on the results of the study, there was an improvement in social skills and student learning outcomes influenced by the use of project-based learning models.